Parental perspectives on school attendance problems and the role of municipal support systems - Hansen, Ulla Irene; Munkhaugen, Ellen Kathrine; Larsen, Kenneth (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionThis study aims to explore parents’ experiences collaborating with support systems in a Norwegian municipality for children who experience school attendance problems (SAP). The heterogeneity of SAP highlights the need for individualized measures tailored to each student's needs and collaboration between schools, municipal support systems, and the Child and Adolescent Psychiatric Outpatient Clinic (BUP). Empowering parents to advocate for their children is crucial in managing challenging situations.MethodIn total, 11 parents of students who received support from a school absenteeism team (SAT) participated in the study. This qualitative study uses focus group interviews as a data collection method.ResultsThe results underscore the complexity of addressing SAP within municipal support systems and the need for a dedicated SAT to support students and empower parents. The parents underline the importance of having collaborative practices, evidence-based knowledge, structures, and procedures to ensure interventions are relevant and predictable. They emphasized the importance of establishing collaborative practices within the municipality.ConclusionCollaborating with parents as equal partners increased the sense of wellbeing for the parents and enhanced the students’ decision-making process.